Peran Guru dalam Proses Pendidikan dan Pembentukan Karakter Peserta Didik di MIN 1 Kutai Timur - Sinar Nurhidayat; Hilyatul Aulia; Muhammad Yasin (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This research aims to examine the strategic role of teachers in the educational process and character building of students at MIN 1 Kutai Timur, as well as to identify supporting and inhibiting factors. Using a descriptive qualitative approach with data collection through observation, interviews, and documentation, the study finds that teachers function as versatile learning facilitators and moral role models. The results indicate that teachers at MIN 1 Kutai Timur do not only transfer academic knowledge but also instill character values such as discipline, honesty, empathy, and responsibility through innovative methods, including group discussions, projects, and the use of educational technology. The implementation of varied teaching methods and personal approaches has proven effective in increasing learning motivation and helping students understand material according to their diverse learning styles. However, teachers face challenges such as heavy administrative burdens, limited resources, and diverse student characters that require special handling. Support in the form of routine supervision from the headmaster and continuous competency training is key to optimizing the teacher's role. Collaboration between teachers, parents, and school administrators is essential to ensure character values are internalized holistically and sustainably.